Effect of Guava Leaf Extract on Aeromonas Hydrophila Bacteria - Jamsuwan Pornpromlikit; Komhom Suchart (Journal of Advances in Medicine and Pharmaceutical Sciences, 2023)
Guava leaves (Psidium guajava L.) contain terpenoids, alkaloids, flavonoids, saponins and tannins, which are believed to have antibacterial properties against Aeromonas hydrophila. Aeromonas hydrophila bacteria are bacteria that are pathogenic and cause systemic disease. This research was conducted to determine the effectiveness of guava leaves in inhibiting Aeromonas hydrophil bacteria. The method used in the antibacterial activity test was the diffusion method using the paper disc technique. The results of the One-Way ANOVA test at the 5% level and followed by the Tukey test showed that the effective inhibitory concentration was 7900 ppm with a moderate antibacterial category.